Pengembangan Subjek Spesifik Pedagogi Berbasis Project Based Learning (PjBL) untuk Menguatkan Literasi Lingkungan Siswa Kelas X MIA SMA - Anik Wulandari; Puguh Karyanto; Suciati Suciati; Muslikhah Irawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The research aims to know about the characteristic, advisability, and effectiveness of Pedagogy Spesific Subject (PSS) equipment based on Project Based Learning (PjBL) to reinforce the students environmental literacy of X science class in senior high school. The researcher used the Research and Development method (R&D). Design of research was using the 3-D model, which was modified from 4-D model Thiagarajan & Stolovich. This research model consists of define, design and develop. The data analysis consists of needs analysis, validation analysis, limited tryout test analysis, subject test analysis, and environmental literacy analysis used the normality test, homogeneity test and non paired sample’s t-Test was helped by SPSS 21 program. The research gives three kinds of result. First, the characteristic of PSS equipment based on PjBL was intregated with NEP dimention and the learning model of PjBL. PSS equipment that was developed is module, lesson plan, student worksheet and evaluation questions. Second, the evidence of validation from expert judgement, substance expert, grammarian, design expert and biology teacher showed that 94,04% in lesson plan (valid), 97,5% in student worksheet (valid), 91,54% in module (valid) and 98,75% in evaluation questions (valid). The result of limited tryout test was 86,6% in module (valid) and 82,5% in student worksheet (valid). The evidence of subject test was 89,9% in module (valid) and 82,5% in student worksheet (valid). Based on validation test results, PSS equipment based on PjBL was valid and can be implemented in biology learning. Third, there were significant differences in student environmental literacy. The result of non paired sample’s t-Test showed that environmental literacy consists of knowledge, attitude and concern aspect have a smaller significance level than ∝(sig.< 0,05), it means that PSS equipment based on PjBL was effective to reinforce students environmental literacy.